Efektivitas Program Pelatihan Dan Pengembangan Sumber Daya Manusia Pada Lembaga Kursus Dan Pelatihan Kinarya Mandiri Jember - Diana Lulita; Siti Zaidatul Khasanah; Nilam Adelia; Fahim Dhiya Ulhaq; Nurul Setianingrum (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the extent to which the human resource training and development program run by the Kinaria Mandiri Jember Course and Training Institute (LKP) is able to provide real impacts for participants. Through a descriptive approach with a combination of quantitative and qualitative methods, data were collected from questionnaires, interviews, and direct observations. The results of the study indicate that the training provided is quite effective in improving the skills and work readiness of participants. Relevant materials, competent instructors, and adequate facilities are the main supporting factors. However, this program still has room for improvement, especially in terms of post-training outcome evaluation and follow-up to alumni. Overall, this program has made a positive contribution to the development of local human resources, and is expected to continue to be developed so that its benefits are wider and more sustainable.